Interatrial differences of basal molecular set‐up and changes in tachycardia‐induced heart failure–a proteomic profiling study. (12th July 2014) - Dietl, Alexander; Winkel, Ingrid; Deutzmann, Rainer; Schröder, Josef; Hupf, Julian; Riegger, Günter; Luchner, Andreas; Birner, Christoph
<x xml:space="preserve">Abstract</x> Aims Left and right atria show compelling differences regarding organogenesis and specific clinical diseases. In congestive heart failure (CHF), remodelling of the atria occurs leading to increased arrhythmogenic susceptibility and deterioration of clinical symptoms. We aimed to assess the basal left and right atrial molecular set‐up and different chamber‐specific atrial changes in heart failure. Methods and results We combined an animal model of rapid ventricular pacing induced heart failure in the rabbit and a gel‐based proteomic screening of left and right atrial specimen. A gene ontology over‐representation analysis was performed for biological function. Ultrastructural adaptations were evaluated using transmission electron microscopy. Comparing left and right atria of healthy control animals (CTRL), 39 proteins displayed significant expression differences involving various biological functions. Upon further statistical analyses, four pathways of energy metabolism were confirmed to be significantly over‐represented beneath the other biological processes. Rapid ventricular pacing induced severe left ventricular systolic dysfunction, symptomatic heart failure and a macroscopic atrial remodelling. In CHF versus CTRL, metabolic and antioxidative enzymes were differentially expressed and showed chamber‐specific bidirectional alterations. Transmission electron microscopy visualized a remarkable and again chamber‐specific ultrastructural disturbance of mitochondrial morphology. Conclusions Our data indicate a diverging basal left and right atrial molecular set‐up in the adult healthy heart. In addition, metabolic and antioxidative enzymes are profoundly and chamber‐specifically altered during atrial remodelling in progressive heart failure.